To find the expression for [tex]\( JL \)[/tex] given that [tex]\( JM = 5x - 8 \)[/tex] and [tex]\( LM = 2x - 6 \)[/tex], we need to add the expressions for [tex]\( JM \)[/tex] and [tex]\( LM \)[/tex].
Step-by-step solution:
1. Write down the given expressions:
[tex]\[
JM = 5x - 8
\][/tex]
[tex]\[
LM = 2x - 6
\][/tex]
2. Add the two expressions together to find [tex]\( JL \)[/tex]:
[tex]\[
JL = JM + LM
\][/tex]
[tex]\[
JL = (5x - 8) + (2x - 6)
\][/tex]
3. Combine like terms:
[tex]\[
JL = 5x + 2x - 8 - 6
\][/tex]
[tex]\[
JL = 7x - 14
\][/tex]
Thus, the expression that represents [tex]\( JL \)[/tex] is:
[tex]\[
7x - 14
\][/tex]
Therefore, the correct answer from the given options is:
[tex]\[
7x - 14
\][/tex]